Determining Temporary Rates for Hospital Health Care Services: An Affirmative Policy Approach - Triono, Agus; Sumarja, FX.; Fakih, Muhammad (Universitas Lampung, 2024)
This research examines the enforcement of the Hospital Director's decision regarding temporary service rates and the authority of the temporary regent to establish these rates within the hospital setting. Employing a normative legal research methodology, the study utilizes both statutory and case approaches at the Regional General Hospital dr. H. Bob Bazar, SKM, in South Lampung Regency, and analyzes the findings descriptively and analytically. The results indicate that the Hospital Director's decision concerning the determination of temporary tariffs is valid until a regional head regulation is issued. In cases where the regional head is unable to fulfill their duties, the temporary regional head is empowered by the Regional Government Law to implement policies related to hospital rates. These actions taken by hospital directors and temporary regional heads are considered affirmative policies aimed at serving the community. However, it is crucial to impose limits on this authority, as legislative approval is necessary to impose costs on the public.